Recognizing individual Bewick’s Swans by bill pattern - Evans, Mary E (Wildfowl, 1977)
The background to the identification by bill pattern of Bewick’s Swans Cygnus columbianus bewickii is given, followed by description of bill pattern development up to and following the third winter. A recognition test demonstrated the reliability of identification by bill pattern, even over a period of years, and that experience of the observer increases proficiency. The problem of storing large numbers of bill patterns are discussed, other clues to identification mentioned, and a recommendation is made that at present identification by bill patterns is better for short rather than long-term studies.